2021
DOI: 10.3390/life11040270
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin and Its Potential Regulatory microRNAs as a Part of Secretome for the Diagnosis of Abnormally Invasive Placenta: Accreta, Increta, and Percreta Cases

Abstract: Magnetic resonance imaging (MRI) and ultrasound methods used for the diagnosis of an abnormally invasive placenta (AIP) have a wide range of sensitivity (Se, 33–93%) and specificity (Sp, 71–100%) levels, which results in a high risk of unfavorable maternal and perinatal outcomes. The relevance of optimizing the diagnosis of AIP is beyond doubt. Given the epigenetic nature of trophoblast invasion, we aimed to quantitate microRNAs and proteins of their target genes that are potentially associated with AIP in blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Disruption of this process can lead to EMT, which can in turn lead to carcinomatosis [45,46]. EMT can be induced by many oncogenic pathways, such as transforming growth factor-β (TGF-β), MAPK, Ras pathway, ERK, PI3K/Akt signaling, and cyclin kinase inhibitor p27mediated signaling [47][48][49]. Reduction or lack of CDH1 expression has been observed in tumors and metastases of many organs, including the gastrointestinal tract, urinary tract, uterus, ovary, thyroid gland, prostate, and skin [43,45,50,51].…”
Section: Cdh1mentioning
confidence: 99%
See 2 more Smart Citations
“…Disruption of this process can lead to EMT, which can in turn lead to carcinomatosis [45,46]. EMT can be induced by many oncogenic pathways, such as transforming growth factor-β (TGF-β), MAPK, Ras pathway, ERK, PI3K/Akt signaling, and cyclin kinase inhibitor p27mediated signaling [47][48][49]. Reduction or lack of CDH1 expression has been observed in tumors and metastases of many organs, including the gastrointestinal tract, urinary tract, uterus, ovary, thyroid gland, prostate, and skin [43,45,50,51].…”
Section: Cdh1mentioning
confidence: 99%
“…Timofeeva et al attempted to develop diagnostic methods for the abnormally invasive placenta (AIP), which includes placenta accreta, percreta, and increta [49]. As we know, trophoblasts require EMT to invade the decidua, which is controlled by multiple signaling pathways, as mentioned earlier.…”
Section: Cdh1mentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-7 plays a role in trophoblasts' invasion via the TGF-β-Smad pathway [ 58 ]. MiR-92a-3p plays a role in endometriosis [ 59 ] and is associated with endometrial receptivity [ 60 ] and trophoblast invasion [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that miRNAs may predict PAS. Recently, scientists have also proven that some microRNAs, such as miR-17-5p, miR-21-5p, miR-25-3p, miR-92a-3p, and miR-320a-3, are associated with severity of PAS ( 23 ). Researchers also found that miRNA can predict PAS prognosis.…”
Section: Biomarkersmentioning
confidence: 99%